2009
DOI: 10.1161/strokeaha.108.541946
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Task-Oriented Circuit Class Training on Walking Competency After Stroke

Abstract: Background and Purpose-There is increasing interest in the potential benefits of circuit class training after stroke, but its effectiveness is uncertain. Our aim was to systematically review randomized, controlled trials of task-oriented circuit class training on gait and gait-related activities in patients with stroke. Methods-A computer-aided literature search was performed to identify randomized, controlled trials in which the experimental group received task-oriented circuit class training focusing on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
147
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(160 citation statements)
references
References 58 publications
1
147
0
8
Order By: Relevance
“…In this study, the consecutive tasks that were applied as an intervention for chronic stroke patients included rising from a from after a sitting posture, for symmetry and active control of the lower limbs and the trunk, and slowly walking forward, sideways, and backward, for active control of the lower limbs and various muscle activities. Furthermore in order to train active lower-limb control and improve gait velocity and coordination, intensive training that included obstacle walking, such as ascending stairs or a slope, and walking backwards on flat ground at maximal speed was conducted 14,17,18) . In addition, this study had subjects perform continuous motions encounterd in daily life, such as holding a cup while standing up from a sitting position, walking while holding a 100 g weight, and climbing up and down a ramp or stairs while moving a cup as described in previous studies of dual-task training the usefulness of which was demonstrated in walking while making a phone call using a cellular phone or holding objects 19) .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the consecutive tasks that were applied as an intervention for chronic stroke patients included rising from a from after a sitting posture, for symmetry and active control of the lower limbs and the trunk, and slowly walking forward, sideways, and backward, for active control of the lower limbs and various muscle activities. Furthermore in order to train active lower-limb control and improve gait velocity and coordination, intensive training that included obstacle walking, such as ascending stairs or a slope, and walking backwards on flat ground at maximal speed was conducted 14,17,18) . In addition, this study had subjects perform continuous motions encounterd in daily life, such as holding a cup while standing up from a sitting position, walking while holding a 100 g weight, and climbing up and down a ramp or stairs while moving a cup as described in previous studies of dual-task training the usefulness of which was demonstrated in walking while making a phone call using a cellular phone or holding objects 19) .…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefits of task-related circuit training after stroke is uncertain 19) , but the program was selected as a good model of a CBR program. According to Salbach 18) , a task-orientated intervention enhances the walking distance and speed of patients who have suffered a stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Lee 15) reported that factors related to motivation in the rehabilitation of patients after a stroke are financial stress, depression, occupation, conjugal affection, and education. Also, the types of CBR programs that have been carried out have mainly been group exercise programs 8,9) , task oriented circuit programs 10,[16][17][18][19] , home visiting programs and the studies of the effects of those programs; but, analyse of these programs has not been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…This small pilot study was the first to describe the effectiveness of group circuit class therapy with regard to improved motor function in people after stroke. Since that time the evidence base has continued to grow and there are now two published systematic reviews on the topic Wevers et al, 2009). …”
Section: Introductionmentioning
confidence: 99%